Impasse in the WTO dispute settlement body: Consequences and responses - Robert McDougall (European Centre for International Political Economy (ECIPE), 2018)
As the United States maintains its block on appointments of new members to the Appellate Body, there is growing concern about the pending incapacitation of the dispute settlement function of the World Trade Organisation. If the WTO can no longer offer effective dispute resolution, some argue, there is a risk that the whole WTO system of rules will collapse. However, while it is important to defend the integrity and effectiveness of dispute resolution, the rules-based system is about more than just the resolution of disputes. What is needed now is measured analyses of the interim options for the WTO if the impasse continues. This Policy Brief reviews some of these options, including the use of "no appeal agreements" and the establishment of alternative plurilateral mechanisms for dispute resolution. It concludes that the alternatives have their own weaknesses and risks, and that the best way forward is for WTO members to pursue constructive and inclusive cooperation in order restore trust in the trade rules and in the good faith of other members.
Keywords: 330